What is a Graph Neural Network in Drug Discovery? The AI Revolution in Pharmaceutical Research - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
What is a Graph Neural Network in Drug Discovery? The AI Revolution in Pharmaceutical Research Introduction: The Challenge of Drug Discovery Drug discov...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation